BIG FIVE PERSONALITY TRAITS AND TEACHING PERFORMANCE OF FACULTY OF COLLEGE OF TEACHER EDUCATION, LAGUNA STATE POLYTECHNIC UNIVERSITY - Tamban, Victoria E.; Banasihan, Gloria L. (International Journal of Research -GRANTHAALAYAH, 2017)
This study aimed to determine the relationships of big five personality traits and teaching performance of faculty of College of Teacher Education, Laguna State Polytechnic University Los Baños Campus, Los Baños, and Laguna. The study was conducted at the College of Teacher Education (CTE) of Laguna State Polytechnic University-Los Baňos Campus during 1st semester of Academic Year 2015-2016 employing correlational research design. The respondents of the study were the 20 faculty of CTE consist of 2 Associate Professors, 10 Assistant Professors and 7 Instructors. A valid survey questionnaire on determining the level of big five personality traits adapted from the site of personality-testing.info, courtesy ipip.ori.org and the IPCR Evaluation are the instruments of this study. Frequency count, percentage and mean were used to describe the profile of the respondents and their teaching performance. Pearson r was used to determine the significant relationship between teachers’’ big five personality traits and their’ teaching performance. The results describe that teachers tend be about average in most of the big five personality traits except from neuroticism which shows a relatively low description. The results also revealed a weak correlation between variables such that it determined that there is no significant relationship the level of big five personality traits and the teaching performance of the respondents. Based on the conclusions the researchers suggested to have further study since it is limited only to the faculty of Teacher Education and also it is highly recommended to correlate teaching performance including students’ evaluation for their teachers and the academic performance of the students with teachers’ personality traits since the teaching performance is one of the factors that affect the students’ academic performance.